Peran Musyrif dalam Mengatasi Problematika Pengasuhan Santri di Pondok Pesantren - Endah Maryani; Muhammad Isa Anshory (Lembaga Yasin AlSys, 2026)
The challenges of student care in Islamic boarding schools are becoming increasingly complex in line with changes in students’ characteristics, developments in digital technology, diverse family backgrounds, and growing demands for the quality of religious guidance and character formation. This condition positions the musyrif as a strategic actor in assisting, guiding, supervising, and resolving various problems in students’ lives. This study aimed to analyse the role of the musyrif in addressing the challenges of student care in Islamic boarding schools and to identify the strategies implemented to create a conducive educational environment. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observations, and documentation studies involving musyrif, Islamic boarding school caregivers, and students. The data were analysed through the stages of data reduction, data presentation, and conclusion drawing, while the credibility of the findings was ensured through triangulation. The results showed that the musyrif performed the roles of educator, mentor, role model, mediator, counsellor, facilitator, and supervisor in addressing problems related to discipline, social adaptation, learning motivation, religious character formation, and students’ mental health. The effectiveness of these roles was supported by interpersonal communication, persuasive approaches, role modelling, continuous guidance, collaboration with Islamic boarding school caregivers and parents, and the implementation of a systematic evaluation system. This study confirms that optimizing the role of the musyrif is an important factor in improving the quality of student care and building an Islamic boarding school environment that is conducive and adaptive to the dynamics of contemporary education. These findings contribute to strengthening student care practices based on mentoring and collaboration and may serve as a reference for Islamic boarding school administrators in developing a more structured and responsive student guidance system.